1998
DOI: 10.1021/la980395o
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolytes Carrying Pendant (Cyanobiphenylyl)oxy Chromophores. Synthesis, Behavior in Aqueous Solution, and Interactions with Surfactants

Abstract: Poly(sulfonylethylmaleic acid monoamide-co-alkyl vinyl ether)s carrying both a sulfonic acid and a carboxylic acid moiety are obtained by reacting the corresponding poly(maleic anhydride-co-alkyl vinyl ether)s with 2-aminoethanesulfonic acid. The alkyl vinyl ethers have a n-hexyl or n-dodecyl group or the alkyl groups have a terminal (cyanobiphenylyl)oxy chromophore and spacer lengths of 6−12 methylene units. Dynamic light scattering experiments show that all polymers form large aggregates in water in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…14. Examples of charged hydrophobically associative polymers used for ESA 54,135,[376][377][378] films and an extremely high roughness. Studies on the use of amphiphilic block copolymers reported poor quality for thicker ESA-films, too, if the hydrophobic block becomes large 374,375) .…”
Section: Polymers Suited For Esamentioning
confidence: 99%
“…14. Examples of charged hydrophobically associative polymers used for ESA 54,135,[376][377][378] films and an extremely high roughness. Studies on the use of amphiphilic block copolymers reported poor quality for thicker ESA-films, too, if the hydrophobic block becomes large 374,375) .…”
Section: Polymers Suited For Esamentioning
confidence: 99%
“…[11] Sodium dodecyl sulfate (SDS, 99.7%) was purchased from Fisher Scientific and was used as received. Background electrolyte buffers for electrokinetic chromatography were prepared at pH 4.0 (10 mM acetate, Aldrich), 7.0 (20 mM TRIS, Sigma) and 9.0 (50 mM Borate, Aldrich).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In many cases, these polymers have properties similar to those of conventional surfactant micelles in that they can solubilize compounds with otherwise low water solubility. [13,14] Applications for such materials have been developed or proposed in drug delivery, detergency, oil recovery and analytical chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations